Plants and Their Bioactive Compounds with the Potential to Enhance Mechanisms of Inherited Cardiac Regeneration - Zhou, Zhen; Li, Dianbin; Zhou, Hua; Lin, Xiaoli; Li, Censing; Tang, Mingfeng; Feng, Zhou; Li, Ming (Planta Medica, 2015)
This article reviews the current progress and research indications in the application of natural plant compounds with the potential for the treatment of cardiovascular diseases. Our understanding of how to apply natural plant compounds to enhance mechanisms of inherited cardiac regeneration, which is physiologically pertinent to myocyte turnover or minor cardiac repair, for substantial cardiac regeneration to repair pathological heart injuries is discussed. Although significant progress has been made in the application of natural plant compounds for therapy of heart diseases, the understanding or the application of these compounds specifically for enhancing mechanisms of inherited cardiac regeneration for the treatment of cardiovascular diseases is little. Recent recognition of some natural plant compounds that can repair damaged myocardial tissues through enhancing mechanisms of inherited cardiac regeneration has offered an alternative for clinical translation. Application of natural plant compounds, which show the activity of manipulating gene expressions in such a way to enhance mechanisms of inherited cardiac regeneration for cardiac repair, may provide a promising strategy for the reconstruction of damaged cardiac tissues due to cardiovascular diseases.
Keywords: natural plant compounds; cardiovascular diseases; myocardial regeneration; mechanisms of inherited cardiac regeneration; cardiovascular diseases; cardiogenin